Remarks to the palaeobiology and taphonomy of illaenid trilobites (Ordovician, Barrandian area, Czech Republic) - Slavickova,J. (Journal of the Czech Geological Society, 1999)
Recent revision of the Family Illaenidae Hawle et Corda, 1847 in the Ordovician of the Prague Basin has resulted in new observation on their palaeoebiology and taphonomy. Concavely bent exoskeletons of Ectillaenus Salter, 1867 are here interpreted as of the exuviation origin rather than reflecting the life position interpreted by several previous authors. Specimens of illaenid trilobites showing possible relationships to some ichnofossils are also reported.
Keywords: Illaenidae; Trilobita; Ordovician; Prague Basin; Bohemia; palaeobiology; exuviation; ichnofossils; taphonomy